PENGARUH CURRENT RATIO, RETURN ON ASSETS, DAN DEBT TO EQUITY RATIOTERHADAP HARGA SAHAM DENGAN TOTAL ASET SEBAGAI VARIABEL MODERASI - Agus Wahyudi; Gos Ishak (CV. Denasya Smart Publisher, 2024)
This research aims to examine the relationship between independent variables, including: Current Ratio,Return on Assets, Debt to Equity Ratio and the dependent variable Stock Price, with the moderatingvariable in this research being Total Assets. Research was conducted on 12 infrastructure companies listedon the Indonesia Stock Exchange (BEI), using non-probability sampling techniques-quota sampling in theperiod 2018 to 2022, a period of 5 years. This study explored whether having good fundamentals wouldhave a direct effect on price increases. the shares of the issuing company are moderated by the condition ofthe company's total assets. The findings of research studies on infrastructure companies show that theCurrent Ratio, if it stands alone, will have a positive effect on share prices, but if it is moderated by totalassets, it will have a negative effect on share prices. Return on Assets has no effect if it stands alone, but ifmoderated by Total Assets then Return on Assets has a positive effect. Debt to Equity Ratio has no effect onshare prices, whether alone or moderated. Simultaneously in this research study, Current Ratio, Return onAssets and Debt to Equity Ratio, moderated by Total Assets, have an effect on stock prices. This study offersa regression analysis on infrastructure companies, the results provide a basis for future research in thisarea. And company management can provide information about the relationship between fundamentalfactors and the company's share price which is moderated by total assets.